1989
DOI: 10.1037/0735-7044.103.4.779
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of an aluminum-induced behavioral deficit by administration of deferoxamine.

Abstract: Administration of aluminum sulfate in the drinking water of male Sprague-Dawley rats for 30 days resulted in a reduction in the number of days to reach extinction criterion on a passive avoidance task (38% control level). The behavioral deficit was not due to nonspecific effects caused by lower fluid consumption. Partial reversal of the deficit was produced by discontinuing aluminum treatment 2 weeks prior to testing (p less than .05). Injection of the aluminum chelator deferoxamine returned the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…These results suggest that co-treatment with quercetin, helped maintain the balance between ROS production and antioxidant defense, as can be inferred from normalized antioxidant enzyme activity values in the combined treatment group. There are reports supporting the protective role of quercetin, against oxidative stress [43][44][45] whereby, quercetin, when administered at a dose of 50 mg/kg to rats, significantly increased SOD activity and decrease MDA level.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that co-treatment with quercetin, helped maintain the balance between ROS production and antioxidant defense, as can be inferred from normalized antioxidant enzyme activity values in the combined treatment group. There are reports supporting the protective role of quercetin, against oxidative stress [43][44][45] whereby, quercetin, when administered at a dose of 50 mg/kg to rats, significantly increased SOD activity and decrease MDA level.…”
Section: Resultsmentioning
confidence: 99%
“…When aluminum exposure was terminated or the aluminum removed by chelation with deferoxamine (Conner et al, 1989;Kruck et al, 1990), the neurotoxic effects were reversed. It has been suggested that aluminum toxicity may contribute to several other diseases, namely Alzheimer disease, Parkinson disease, and amyotrophic lateral sclerosis-Parkinsonism-dementia of Guam.…”
Section: Introductionmentioning
confidence: 99%
“…CpH is considered as a cholinergic drug that gets hydrolyzed in vivo into two components DMAE and PCPA. DMAE serves as an important precursor of choline and hence may contribute to increased ACh levels, which in turn increases AChE activity [19]. Several authors linked the reduction of ACh with short-term memory disturbance, which may result in incomplete understanding and consequently abnormal communication skills as seen in our studies.…”
Section: Discussionmentioning
confidence: 88%
“…Long-term exposure of Al for 8 weeks resulted in a significant impairment in memory and learning ability. Connor et al [19] demonstrated impaired performance of rats on a passive avoidance task after administration of Al in drinking water. Similarly, Schwartz et al [20] suggested that cognitive function may progressively decline because of post-occupational exposure to a neurotoxicant.…”
Section: Discussionmentioning
confidence: 98%